Qianjinweijing Decoction Protects Against Fine Particulate Matter Exposure-mediated Lung Function Disorder - Chen, Rucheng; Zhang, Jinna; Pang, Yaxian; Liu, Qingping; Peng, Jing; Lin, Xiujuan; Cao, Lingyong; Gu, Weijia; Zhang, Lu; Li, Ran; Sun, Qinghua; Zhang, Rong; et al. (Frontiers in Pharmacology, 2022)
Fine particulate matter (PM2.5) is well known to impair lung function. Strategies protecting against PM2.5-exerted lung dysfunction have been less investigated. Qianjinweijing decoction (QJWJ), the decoction of herbal medicine from natural origion, has been used to treat lung disorders as it downregulates oxidation and inflammation. However, no clinical trial has yet evaluated the role of QJWJ in PM2.5-induced lung dysfunction. Therefore, we conduct a randomized, double-blind, placebo-controlled trial to assess whether QJWJ provided lung benefits against the adverse effects of PM2.5 exposure among adults. Eligible participants (n=65) were recruited and randomized to receive QJWJ decoction (n=32) or placebo (n=33) for 4 weeks. The restrictive ventilatory defect (RVD), lung function parameters, and induced sputum were collected from participants and analyzed. PM2.5 exposure concentration was significantly associated with the vital capacity, peak expiratory flow and forced expiratory flow at 75% of the forced vital capacity. The negative association between PM2.5 and lung function parameters was eliminated in response to QJWJ intervention. Additionally, the percentage of RVD (P=0.018) and the proportion of eosinophils (Eo%) in induced sputum (P=0.014) in the QJWJ group was significantly lower in QJWJ group than in the placebo group. This study demonstrated that QJWJ could alleviate PM2.5-induced lung dysfunction and might be a potential treatment for air pollution-related chronic respiratory diseases. Clinical Trial Registration: www.chictr.org.cn, identifier ChiCTR2000039210.